Electronic and paper mode of data capture when assessing patient‐reported outcomes in the National Dental Practice‐Based Research Network. Issue 4 (2nd June 2019) - Kopycka‐Kedzierawski, Dorota T.; Cacciato, Rita; Hennessey, Roslyn; Meyerowitz, Cyril; Litaker, Mark S.; Heft, Marc W.; Johnson, Kimberly S.; Reyes, Stephanie C.; Johnson, James D.; Baltuck, Camille T.; Gilbert, Gregg H.; ,
Abstract: Aim: Our objectives were to describe the approach used in the National Dental Practice‐Based Research Network to capture patient‐reported outcomes and to compare electronic and paper modes of data capture in a specific network study. Methods: This was a prospective, multicenter cohort study of 1862 patients with dentin hypersensitivity. Patient‐reported outcomes were assessed based on patients' perception of pain using Visual Analog Scales and Labeled Magnitude scales at baseline and at 1, 4 and 8 weeks post‐baseline. Results: Eighty‐five percent of study patients chose to complete follow‐up assessments via an electronic mode; 15% completed them via a paper mode. There was not a significant difference in the proportions of patients who completed the 8‐week assessment when comparing the electronic mode to the paper mode (92% vs. 90.8%, P  = 0.31, Rao‐Scott clustered χ 2 ‐test). Conclusion: The electronic mode of data capture was as operational as the traditional paper mode, while also providing the advantage of eliminating data entry errors, not involving site research coordinators in measuring the patient‐reported outcomes, and not incurring cost and potential delays due to mailing study forms. Electronic data capture of patient reported outcomes could be successfully implemented in the community dental practice setting.